A cross‐sectional study to quantify the prevalence of avian influenza viruses in poultry at intervention and non‐intervention live bird markets in central Vietnam, 2014. Issue 6 (24th January 2017) - Chu, D.‐H.; Stevenson, M. A.; Nguyen, L. V.; Isoda, N.; Firestone, S. M.; Nguyen, T. N.; Nguyen, L. T.; Matsuno, K.; Okamatsu, M.; Kida, H.; Sakoda, Y.
Summary: In Vietnam, live bird markets are found in most populated centres, providing the means by which fresh poultry can be purchased by consumers for immediate consumption. Live bird markets are aggregation points for large numbers of poultry, and therefore, it is common for a range of avian influenza viruses to be mixed within live bird markets as a result of different poultry types and species being brought together from different geographical locations. We conducted a cross‐sectional study in seven live bird markets in four districts of Thua Thien Hue Province in August and December, 2014. The aims of this study were to (i) document the prevalence of avian influenza in live bird markets (as measured by virus isolation); and (ii) quantify individual bird‐, seller‐ and market‐level characteristics that rendered poultry more likely to be positive for avian influenza virus at the time of sale. A questionnaire soliciting details of knowledge, attitude and avian influenza practices was administered to poultry sellers in study markets. At the same time, swabs and faecal samples were collected from individual poultry and submitted for isolation of avian influenza virus. The final data set comprised samples from 1, 629 birds from 83 sellers in the seven live bird markets. A total of 113 birds were positive for virus isolation; a prevalence of 6.9 (95% CI 5.8–8.3) avian influenza virus‐positive birds per 100 birds submitted for sale. After adjusting for clustering at the market and individual seller levels, none of the explanatory variables solicited in the questionnaire were significantly associated with avian influenza virus isolation positivity. The proportions of variance at the individual market, seller and individual bird levels were 6%, 48% and 46%, respectively. We conclude that the emphasis of avian influenza control efforts in Vietnam should be at the individual seller level as opposed to the market level.